PENGARUH PENGGUNAAN BAHAN AJAR MATEMATIKA BERSUPLEMEN KOMIK TERHADAP KEMANDIRIAN BELAJAR SISWA - mochamad guntur; Arif Muchyidin; widodo winarso (EduMa: Mathematics education learning and teaching, 2017)
Mathematics is a lesson that many students do not like, so to change it all required interactive teaching materials that can foster student self-reliance. The purpose of this research is to know whether there is influence of response of the use of mathematics material supplement comic to student self-reliance. The method used in this research is descriptive statistical method with research design The One-Shot Case Study Design. The result of hypothesis obtained Fcount = 17,198 and Ftable = 3,14 based on Ha hypothesis criteria.Â Keywords: Teaching Materials, Comic Mathematics, Independence.